Opportunities for improving the efficiency of keratinocyte carcinoma care in primary and specialist care: Results from population-based Dutch cohort studies. (August 2019) - Wakkee, M.; van Egmond, S.; Louwman, M.; Bindels, P.; van der Lei, J.; Nijsten, T.; Hollestein, L.
Abstract: Background: High incidence rates of keratinocyte carcinoma (KC) in Western countries put pressure on healthcare systems. The aim of this study was to describe clinical practice in order to identify areas for improvement. Methods: A random selection of patients from the Integrated Primary Care Information database who consulted their general practitioner (GP) for suspicious or confirmed KC (n = 1597) was made in the analysis. For secondary care, 1569 patients with histologically confirmed KC were randomly selected from the Netherlands Cancer Registry. All patients were diagnosed between 2009 and 2013 and followed up until 2016. Details on diagnosis, treatment and care during follow-up were described. Results: Among 942 patients who consulted their GP, KC was included in the working or differential diagnosis, but two-thirds (629) were not KC. If the GP suspected KC, the GP directly referred to a medical specialist in most cases (548 of 942). In half (470 of 967) of all confirmed KCs, a skin malignancy was not described in the initial working or differential diagnosis of the GP. The medical specialist treated the first primary KC in 86% (1369 of 1596) by excision, 4% (69 of 1596) by Mohs surgery and 10% (158 of 1596) by another treatment. Although follow-up is not recommended for low-risk basal cell carcinoma, 83% (29 of 35) received follow-up care. In contrast, 82% (60 of 73) patients with squamous cell carcinoma received less follow-up than recommended. Conclusions: Strengthening the diagnostic pathway for KC in primary care and reduction of low-value follow-up visits in secondary care seem potential areas for improving the efficiency of KC care. Highlights: In primary care, 67% of suspected keratinocyte cancers (KCs) were not KC. In primary care, KC was not included in the initial diagnosis in 49% of all confirmed KC. In secondary care, 83% of low-risk patients with basal cell carcinoma received too frequent follow-up visits. In secondary care, 82% of all patients with squamous cell carcinoma received too few follow-up visits.